2019
DOI: 10.1021/acscentsci.9b00551
|View full text |Cite
|
Sign up to set email alerts
|

A Localized Chimeric Hydrogel Therapy Combats Tumor Progression through Alteration of Sphingolipid Metabolism

Abstract: Rapid proliferation of cancer cells assisted by endothelial cell-mediated angiogenesis and acquired inflammation at the tumor microenvironment (TME) lowers the success rate of chemotherapeutic regimens. Therefore, targeting these processes using localized delivery of a minimally toxic drug combination may be a promising strategy. Here, we present engineering of a biocompatible self-assembled lithocholic acid-dipeptide derived hydrogel (TRI-Gel) that can maintain sustained delivery of antiproliferating doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 63 publications
2
63
0
Order By: Relevance
“…Any traces of genomic DNA were removed by DNase (Invitrogen, Am2238) treatment for 30 min at 37 °C followed by heat inactivation using 50 mM EDTA (Sigma, E5134). cDNA synthesis and real-time PCR were done as described previously 27 . Relative quantitation of gene expression was done using β -actin as the endogenous reference gene for normalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any traces of genomic DNA were removed by DNase (Invitrogen, Am2238) treatment for 30 min at 37 °C followed by heat inactivation using 50 mM EDTA (Sigma, E5134). cDNA synthesis and real-time PCR were done as described previously 27 . Relative quantitation of gene expression was done using β -actin as the endogenous reference gene for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group has shown that a combination chemotherapy induces the AS in glucocerebrosidase β ( Gba1 ), and increases Gba1 expression in murine tumor tissues. This enhanced Gba1 expression catalyzes the degradation of glucosylceramides to ceramides responsible for tumor regression, and lowers the glucosylceramide levels critical for drug resistance 27 .…”
Section: Introductionmentioning
confidence: 99%
“…For lung cancer treatment, CA4 could also cooperate with other elements. Sanjay Pal et al 133 synthesized a self‐assembled lithocholic acid‐dipeptide hydrogel (TRI‐Gel) for co‐delivery of DOX, CA4, and dexamethasone (DEX). Beyond the anticancer effect of DOX and the antiangiogenesis of CA4, the anti‐inflammatory function of DEX contributed to the abrogation of carcinoma tissue.…”
Section: The Application Of Hydrogels In Localized Tumor Treatmentmentioning
confidence: 99%
“…Sustained release of these drugs resulted in increased apoptosis, reduced inflammation and inhibition of angiogenesis, all of which led to increased survival rate in a murine tumor model, indicating the synergistic effect of multiple drugs. [104] Off-target delivery of drugs results in undesirable toxicity to healthy cells. Appropriate carriers are able to overcome such challenges.…”
Section: (20 Of 38)mentioning
confidence: 99%